Parameter Analysis Of A Remotely Controlled Home Monitoring System Using Mobile Robot Via Camera - Md Ghazaly, Mariam; Ho, Carl Choon; Jamaludin, Irma Wani; Soo, Kok Yew; Yaacob, Mohd Rusdy; Abdullah, Zulkeflee; Md Ali, Mohd Amran (Penerbit UTM Press, 2017)
In this paper, the performance and prototype of a remotely-controlled home monitoring mobile robot for security and surveillance purposes were discussed. Home monitoring system has been one of the basic infrastructures that is being used in most of the residential compound. However, traditional CCTV system, which requires supporting surfaces and high equipment cost, has forced human to search for an alternative. Thus, this project provided a more flexibility and mobility to the home monitoring system, which consisted of an obstacle detection system and a camera. After discussing the conception of the project, as part of the experiment aspect method, experiment setup and result were presented. In this paper, the objectives also looked into the sensitivity of the obstacle avoidance system, to design and develop a remotely-controlled home monitoring robot, to design and develop a networking system for long distance robot control and to analyze the performance of the motor in terms of pulse width modulation (PWM). In conclusion, the experimental result proved that the proposed project was successfully developed with detailed supporting data.